The evolution of Belarusian public sector: From command economy to state capitalism? - Aliaksandr Papko; Piotr Kozarzewski (Center for Social and Economic Research (CASE), 2020)
Belarus was among the few post-communist countries to resign from comprehensive market reforms and attempt to improve the efficiency of the economy through administrative means, leaving market mechanisms only an auxiliary role. Since its inception, the 'Belarusian economic model' has undergone several revisions of a de-statisation and de-regulation kind, but still the Belarusian economy remains dominated by the state. This paper analyses the characteristic features of the Belarusian economic system - especially those related to the public sector - as well as its evolution over time during the period following its independence. The paper concludes that during the post-Soviet period, the Belarusian economy evolved from a quasi-Soviet system based on state property, state planning, support to inefficient enterprises and the massive redistribution of funds to a more flexible hybrid model where the public sector still remains the core of the economy. The case of Belarus shows that presently there is no appropriate theoretical perspective which, in an unmodified form, could be applied to study this type of economic system. Therefore, a new perspective based on an already existing but updated approach or a multidisciplinary approach that incorporates the duality of the Belarusian economy is required.
Keywords: L53; O17; P21; P31; 330; state-owned enterprises; post-communist transition; state capitalism; institutions; Belarus